2007
DOI: 10.1088/0957-4484/18/40/405305
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of In-rich InGaN nanodots grown by metallo-organic chemical vapor deposition

Abstract: The surface morphologies, alloy compositions and emission properties of In-rich In x Ga 1−x N nanodots (x 0.87) grown by metallo-organic chemical vapor deposition at various growth temperatures (550-750 • C) were investigated. We found that the nucleation of InGaN dots was dominated by the surface migration of In adatoms. A higher Ga content can be achieved at lower growth temperatures due to the relatively lower migration ability of Ga adatoms. At higher growth temperatures, the InGaN dots tend to decompose i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The bond strength of In-N (7.7 eV/atom) is weaker than that of Ga-N (8.9 eV/atom), so the indium adatoms are expected to migrate more easily than Ga adatoms and dominate the migration process, resulting in a higher indium composition of QDs than that of the planar epilayer. 11) Hence, the InGaN PL wavelength increases from 466 to 500 nm. The average density, diameter, and height are 2:0 Â 10 9 cm À2 , 70 nm, and 8 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bond strength of In-N (7.7 eV/atom) is weaker than that of Ga-N (8.9 eV/atom), so the indium adatoms are expected to migrate more easily than Ga adatoms and dominate the migration process, resulting in a higher indium composition of QDs than that of the planar epilayer. 11) Hence, the InGaN PL wavelength increases from 466 to 500 nm. The average density, diameter, and height are 2:0 Â 10 9 cm À2 , 70 nm, and 8 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7][8][9] Investigations on high-indium-composition QDs emitting longer wavelengths are much fewer. 1,10,11) For InGaN-based green and red light emitting devices, QWs are suffering from poor material quality and the quantum-confined Stark effect induced by the large lattice mismatch. Growth of InGaN QDs to replace the QWs is a promising method to weaken the influence mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…However, we found that it is probably the decomposition and re-incorporation of InGaN that leads to the formation of QDs. Early studies generally suggest that the InGaN decomposition is mainly attributed to the small In–N bonding energy, which allows the In–N bond to easily decompose and migrate, so the indium composition of InGaN QDs is higher than that of WL. However, recent studies have shown that the decomposition region of InGaN may be a metastable or unstable region formed by phase separation …”
Section: Resultsmentioning
confidence: 99%
“…Statistical analysis of number density (ρ), mean grain size ( R ), the ratio of mean volume ( V ) to mean project area ( A p ), the roughness of root mean square (RMS) for 5 µm × 5 µm and the ratio of project area and total area (A t ). and especially In-N, will be broken, which is attributed to the fact that the bond strength of In-N (7.7 eV/atom) is lower than that of Ga-N (8.9 eV/atom) [20]. This breakage leads to three effects: (1) thin InN platelets are immersed in the flat GaN layer and dissolve themselves through diffusion, and this result in an increase in project area (table 1); (2) large InN dots merge with small dots to form larger InN dots; (3) the interdiffusion between the flat GaN layer and InN dot results in InGaN dots.…”
Section: Resultsmentioning
confidence: 99%